2017
DOI: 10.29252/ijmr-040105
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vitamins and Trace Elements on Oral Health: A Systematic Review

Abstract: Introduction: Nutritional guidance is one of the very important components of preventive dentistry today. To prevent oral, dental and craniofacial diseases, one approach is having a suitable diet. Hence, the aim of this review was to provide a concise, didactic update on the role of vitamin and trace elements on various aspects of oral health and diseases. Methods: Literature search was carried out electronically through Google scholar, Pubmed and Ebsco data base and there was no time frame limitation set for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Vitamin D has been related to gingival inflammation [47] and tooth loss [17,19,20,25,33,35,36]. Moreover, vitamins and in particular vitamin D as a promising oral health-preventive agent were the object of several previous reviews [73][74][75][76][77], systematic [74][75][76] and narrative [73,77] leading to a low-certainty conclusion that vitamins may reduce the incidence of caries and periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D has been related to gingival inflammation [47] and tooth loss [17,19,20,25,33,35,36]. Moreover, vitamins and in particular vitamin D as a promising oral health-preventive agent were the object of several previous reviews [73][74][75][76][77], systematic [74][75][76] and narrative [73,77] leading to a low-certainty conclusion that vitamins may reduce the incidence of caries and periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, vitamin C contributes to collagen synthesis, which is an important protein for providing tooth structure, support, and maintenance (25,26). Vitamin C induces calcium deposition, mineralization, and reduces the risk of developing secondary caries in children (27). In a meta-analysis conducted to review dietary factors associated with dental erosion, Li et al revealed that chewing vitamin C tablets was significantly associated with tooth wear development (28) partly due to its low pH.…”
Section: Vitamin C and Oral Healthmentioning
confidence: 99%
“…Therefore, an endeavor to maintain optimal conditions and enhance oral health necessitates the implementation of supplemental nutritional therapy, which is beneficial to the patients [ 11 ]. There are positive associations between particular nutrients, such as calcium, vitamins C and D, and periodontal health [ 12 ].…”
Section: Introductionmentioning
confidence: 99%